2020
DOI: 10.3390/ma13184094
|View full text |Cite
|
Sign up to set email alerts
|

Cryogenic Drilling of AZ31 Magnesium Syntactic Foams

Abstract: Machined surface quality and integrity affect the corrosion performance of AZ31 magnesium composites. These novel materials are preferred for temporary orthopedic and vascular implants. In this paper, the drilling performance of AZ31-magnesium reinforced with hollow alumina microsphere syntactic foam under LN2 cryogenic, dry, and Almag® Oil is presented. Cutting tests were conducted using TiAlN physical vapor deposition (PVD) coated multilayer carbide and K10 uncoated carbide twist drills. AZ31 magnesium matri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Bolat et al (2022) conducted machining work on the pumice-reinforced foams and concluded that cutting force values diminished depending on the increasing cutting speeds due to the thermal softening of the matrix and the fragile nature of SiO 2 -based particles. Kannan et al (2020b) tended to cryogenic machining of the AZ31 syntactic foams and enounced that better surfaces could be achieved through low-temperature cutting. The same team offered a mechanistic model to MMMS 20,3 explicate the load/deformation transfer between AZ91 foam constituents (Kannan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Bolat et al (2022) conducted machining work on the pumice-reinforced foams and concluded that cutting force values diminished depending on the increasing cutting speeds due to the thermal softening of the matrix and the fragile nature of SiO 2 -based particles. Kannan et al (2020b) tended to cryogenic machining of the AZ31 syntactic foams and enounced that better surfaces could be achieved through low-temperature cutting. The same team offered a mechanistic model to MMMS 20,3 explicate the load/deformation transfer between AZ91 foam constituents (Kannan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Even though this investigation revealed the effect of the filler particle size on the machining force of the metallic foams, utilized bubble alumina spheres can be interpreted as expensive compared to other alternative fillers. On the other side, cryogenic machining applications have been popular among investigators and this approach has been applied to the alumina-filled magnesium composite foams to obtain the better surface quality of the machined parts [23]. In addition to these findings, cryogenic machining leads to thrust force increasing that influences tool life negatively although it helps attain lower surface roughness values on the machined surfaces.…”
Section: Introductionmentioning
confidence: 99%